Avaliação dos níveis de resposta das emissões otoacústicas em neonatos com asfixia perinatal - Ribeiro, Georgea Espindola [UNESP]; Silva, Daniela Polo Camargo da [UNESP]; Montovani, Jair Cortez [UNESP] (My University, 2014)
Objective: To evaluate the effects of perinatal asphyxia on the level of the response to transient otoacoustic emissions in infants. Methods: Otoacoustic emissions in 154 neonates were performed: 54 infants who suffered asphyxia at birth, measured by Apgar score and medical diagnosis, and 100 infants without risk were compared. Scores less than 4 in the first minute and/or less than 6 in the fifth minute were considered as “low Apgar”. Statistical analysis of the data was performed using the Kruskal, Wilcoxon, and Mann-Whitney nonparametric tests. Results: Lower levels of response were observed in transient otoacoustic emission in the group that suffered perinatal asphyxia, with significant values for the frequencies 2,000, 3,000, and 4,000 Hz in the right ear, and 2,000 and 4,000 Hz in the left ear. Conclusions: The analysis of the intrinsic characteristics of the otoacoustic emissions evidenced low performance of outer hair cells in neonates who had perinatal asphyxia, which may affect the development of listening skills in this population.
Assessment of levels of otoacoustic emission response in neonates with perinatal asphyxia
Keywords: Apgar score; Asphyxia neonatorum; Neonatal screening